An artificial neural network model based on standing lateral radiographs for predicting sitting pelvic tilt in healthy adults - Zhao, Minwei; He, Yuanbo; Li, Shuai; Chen, Huizhu; Li, Weishi; Tian, Hua (Frontiers in Surgery, 2022)
Background: Spinopelvic motion, the cornerstone of the sagittal balance of the human body, is pivotal in patient-specific total hip arthroplasty. Purpose: This study aims to develop a novel model using back propagation neural network (BPNN) to predict pelvic changes when one sits down based on standing lateral spinopelvic radiographs. Methods: Young healthy volunteers were included in, 18 spinopelvic parameters were taken, such as pelvic incidence (PI) and so on. First, standing parameters correlated with sitting PT and SS were identified via Pearson correlation. Then, with these parameters as inputs and sitting PT and SS as outputs, the BPNN prediction network was established. Finally, the prediction results were evaluated by relative error (RE), prediction accuracy (PA), normalized root mean squared error (NRMSE). Results: The study included 145 volunteers of 23.1±2.3 years old(M:F=51:94). Pearson analysis revealed sitting PT was correlated with six standing measurements and sitting SS with five. The best BPNN model achieved 78.48% and 77.54% accuracy in predicting PT and SS; As for PI, a constant for pelvic morphology, was 95.99%. Discussion: In this study, the BPNN model yielded desirable accuracy in predicting sitting spinopelvic parameters, which provides new insights and tools for characterizing spinopelvic changes throughout the motion cycle.